2-Quasi-prime modules - Jasem, Fatima Dhiyaa; Elewi, Alaa A. (Iraqi Journal of Science, 2023)
We introduce in this paper, the notion of a 2-quasì-prime module as a generalization of quasi-prime module, we know that a module E over a ring R is called quasi-prime module, if (0) is quasi-prime submodule. Now, we say that a module E over ring R is a 2-quasi-prime module if (0) is 2-quasi-prime submodule, a proper submodule K of E is 2-quasi-prime submodule if whenever , and , then either or . Many results about these kinds of modules are obtained and proved, also, we will give a characterization of these kinds of modules.